Evaluation of image quality and radiation dose of abdominal dual-energy CT. (July 2018) - Schmidt, David; Söderberg, Marcus; Nilsson, Mats; Lindvall, Håkan; Christoffersen, Christina; Leander, Peter
Background: Dual-energy computed tomography (DECT) has conceptually been known since the late 1970s and commercially available as dual-source CT (DSCT) systems since 2006; however, the technique has not yet seen widespread implementation in routine protocols. Part of the cause for this is likely due to misconceptions about radiation dose and/or image quality when using DECT. Purpose: To compare image quality and radiation dose of single-energy CT (SECT) and DECT abdominal examinations obtained in clinical practice on a second generation DSCT. Material and Methods: A total of 495 included patients (mean age = 70.9 years) were retrospectively analyzed after undergoing either SECT (120 kVp and age-based mAs) or DECT examinations (80/Sn140 kVp and age-based mAs). The patients were divided into two groups based on examination type (247 SECT, 248 DECT), which were then subdivided into two groups, each based on age. Image noise was measured in the liver and image quality was subjectively assessed in 100 randomly selected patients. Results: Noise levels were significantly lower in DECT (13.9 HU) compared with SECT (14.7 HU) ( P < 0.05). No significant differences in subjective image quality were found between DECT and SECT, except for one criterion in the 50–74-year age group. The mean dose-length product (DLP) (376 mGy-cm) and effective dose (6.1 mSv) of DECT were significantly lower than the DLP (513 mGy-cm) and effective dose (8.4 mSv) of SECT ( P < 0.05). Conclusion: DECT can be implemented in routine clinical use without negatively impacting image quality while lowering radiation dose to the patient.